2017
DOI: 10.1111/jfpp.13328
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the nutritional values, volatiles compounds, and sensory qualities of pea pastes cooked in iron pot and clay pot

Abstract: In the current study, the nutritional values, volatiles compounds, and sensory qualities of pea pastes cooked in iron pot and clay pot were compared. Results showed that the iron pot‐cooked pea pastes contained profoundly more iron, total sugar, and starch than the clay pot‐cooked ones, and the effects were found related to iron ion by comparing the results between clay pot‐cooked pastes with and without iron ion addition. Samples prepared with the two utensils demonstrated similar contents of protein, polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The initial literature search resulted in total 123 articles, from which 13 articles were finally included for the systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32]. The PRISMA flow diagram of selection and exclusion of studies is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial literature search resulted in total 123 articles, from which 13 articles were finally included for the systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32]. The PRISMA flow diagram of selection and exclusion of studies is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies except one were conducted outside India [20]. Four studies were reported from Cambodia [19][20][21][22], two studies from Malawi [23][24], two from Brazil [25][26], one study each from Ethiopia [27], Benin [28], China [29] and USA [30]. Randomized, non-randomized or basic experimental trials on iron content of food items, published between 1991 to 2020 were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of variance (ANOVA) and the Duncan multiple range test were used to compare the means for color and texture. Xing, Xing, Zhang, Hu, and Liu (), using the one‐way ANOVA and t test, investigated whether cooking in iron pot could have influence on the sensory properties of pea pastes in comparison with cooking in clay pot. However, the standard errors and tests in these classical methods rest on the assumption that the response, conditional on the explanatory variables follows the normal distribution, which it is not the case, for discrete response and in particular for ratings scales with a small number of categories (Christensen & Brockhoff, ).…”
Section: Introductionmentioning
confidence: 99%